Regulation of Human Hsc70 ATPase and Chaperone Activities by Apg2: Role of the Acidic Subdomain. Issue 2 (18th January 2019) - Cabrera, Yovana; Dublang, Leire; Fernández-Higuero, José Angel; Albesa-Jové, David; Lucas, Maria; Viguera, Ana Rosa; Guerin, Marcelo E.; Vilar, Jose M.G.; Muga, Arturo; Moro, Fernando
Abstract: Protein aggregate reactivation in metazoans is accomplished by the combined activity of Hsp70, Hsp40 and Hsp110 chaperones. Hsp110s support the refolding of aggregated polypeptides acting as specialized nucleotide exchange factors of Hsp70. We have studied how Apg2, one of the three human Hsp110s, regulates the activity of Hsc70 (HspA8), the constitutive Hsp70 in our cells. Apg2 shows a biphasic behavior: at low concentration, it stimulates the ATPase cycle of Hsc70, binding of the chaperone to protein aggregates and the refolding activity of the system, while it inhibits these three processes at high concentration. When the acidic subdomain of Apg2, a characteristic sequence present in the substrate binding domain of all Hsp110s, is deleted, the detrimental effects occur at lower concentration and are more pronounced, which concurs with an increase in the affinity of the Apg2 mutant for Hsc70. Our data support a mechanism in which Apg2 arrests the chaperone cycle through an interaction with Hsc70(ATP) that might lead to premature ATP dissociation before hydrolysis. In this line, the acidic subdomain might serve as a conformational switch to support dissociation of the Hsc70:Apg2 complex. Graphical abstract: Unlabelled Image Highlights: Human Apg2 supports protein aggregate reactivation acting as nucleotide exchange factor of Hsc70. Regulation of Hsc70 binding to aggregates by Apg2 correlates with substrate reactivation. Apg2 stimulates/inhibits the activity of the Hsc70 system in a concentration-dependent manner. An Hsc70:Apg2 complex arrests the ATPase cycle in the ADP/ATP exchange process. The acidic subdomain supports dissociation of the Hsc70:Apg2 complex.